Modulation of electrocatalytic activity by tuning anion electronegativity: case study with copper chalcogenides - Harish Singh; David Prendergast; Manashi Nath (JPhys Energy, 2023)
Anion-tuning in metallic chalcogenides has been shown to have a significant impact on their electrocatalytic ability for overall water splitting. In this article, copper-based chalcogenides (Cu _2 X, X = O, S, Se, and Te) have been systematically studied to examine the effect of decreasing anion electronegativity and increasing covalency on the electrocatalytic performance. Among the copper chalcogenides, Cu _2 Te has the highest oxygen evolution reaction (OER) activity and can sustain high current density of 10 and 50 mA cm ^−2 for 12 h. The difference in intrinsic catalytic activity of these chalcogenide surfaces have been also probed through density functional theory calculations, which was used to estimate energy of the catalyst activation step. It was observed that the hydroxyl adsorption on the surface catalytic site is critically important for the onset and progress of OER activity. Consequently, it was also observed that the –OH adsorption energy can be used as a simple but accurate descriptor to explain the catalytic efficiency through volcano-like correlation plot. Such observation will have a significant impact on developing design principle for optimal catalytic surface exhibiting high performance as well as prolonged stability.